2018
DOI: 10.1016/j.cortex.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Beyond time and space: The effect of a lateralized sustained attention task and brain stimulation on spatial and selective attention

Abstract: The Theory of Visual Attention (TVA) provides a mathematical formalisation of the "biased competition" account of visual attention. Applying this model to individual performance in a free recall task allows the estimation of 5 independent attentional parameters: visual short-term memory (VSTM) capacity, speed of information processing, perceptual threshold of visual detection; attentional weights representing spatial distribution of attention (spatial bias), and the top-down selectivity index. While the TVA fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 100 publications
0
10
0
1
Order By: Relevance
“…The effect of tRNS, at least when applied within the 0.75-mA to 2-mA range, is believed to be excitatory because of the fast-oscillating electrical fields putatively depolarizing neurons irrespective of the current polarity (Fertonani & Miniussi, 2017; Terney, Chaieb, Moliadze, Antal, & Paulus, 2008; but see Parkin, Bhandari, Glen, & Walsh, 2019). Studies have demonstrated the potential for tRNS to modulate a range of capacities from motor (Terney et al, 2008) and sensory (van der Groen & Wenderoth, 2016), to cognitive abilities such as arithmetic learning (Snowball et al, 2013), selective attention (Shalev, De Wandel, Dockree, Demeyere, & Chechlacz, 2018), adaptive reasoning (Brem et al, 2018), and procedural learning (Frank, Harty, Kluge, & Cohen Kadosh, 2018).…”
mentioning
confidence: 99%
“…The effect of tRNS, at least when applied within the 0.75-mA to 2-mA range, is believed to be excitatory because of the fast-oscillating electrical fields putatively depolarizing neurons irrespective of the current polarity (Fertonani & Miniussi, 2017; Terney, Chaieb, Moliadze, Antal, & Paulus, 2008; but see Parkin, Bhandari, Glen, & Walsh, 2019). Studies have demonstrated the potential for tRNS to modulate a range of capacities from motor (Terney et al, 2008) and sensory (van der Groen & Wenderoth, 2016), to cognitive abilities such as arithmetic learning (Snowball et al, 2013), selective attention (Shalev, De Wandel, Dockree, Demeyere, & Chechlacz, 2018), adaptive reasoning (Brem et al, 2018), and procedural learning (Frank, Harty, Kluge, & Cohen Kadosh, 2018).…”
mentioning
confidence: 99%
“…To our knowledge, we present the first evidence for perceptual benefits of temporal expectation in CPT independent of motor preparation. Our tasks placed no emphasis on motor performance: In Experiment 1, we used a task that yielded individual differences in perceptual parameters by using forward and backward masking (Shalev, De Wandel, Dockree, Demeyere, & Chechlacz, 2017;Shalev et al, 2016;Shalev, Humphreys, & Demeyere, 2018;Shalev, Vangkilde, et al, 2019). In Experiment 2, participants performed fine perceptual discriminations.…”
Section: Discussionmentioning
confidence: 99%
“…The mathematical implementation of the TVA model enables estimation of five theoretical parameters: visual short-term memory capacity, processing speed, perceptual threshold, spatial bias and top-down selectivity index (see methods section for full details; Bundesen, 1990, Kyllingsbaek, 2006; Kyllingsbaek et al, 2011). Importantly, it has been previously shown that attentional selectivity and capacity measures derived in accordance with the TVA model are unrelated to sustained attention measures (McAvinue et al, 2012, Shalev et al, 2018a). This ensures that the tasks employed here indeed provide measures of distinct, independent attention functions.…”
Section: Introductionmentioning
confidence: 94%